FREQUENCY AND PATTERN OF SUBSTANCE MISUSE IN PATIENTS WITH SCHIZOPHRENIA - Shakeel, Muhammad; Adeela; Ali, Akhtar (Journal of Postgraduate Medical Institute, 2021)
Objective: To determine the frequency and pattern of substance misuse in patients with schizophrenia Methodology: A total of 425 patients with schizophrenia, as per International Classification of Diseases Research criteria version 10 (ICD-10), were included in this cross sectional study from Sarhad Hospital for Psychiatric Diseases Peshawar from September 2020 to February 2021. Patients Information was gathered through a semi-structured questionnaire. Frequency and percentage for categorical variables while mean and standard deviation for continuous variables were calculated using SPSS version 24. Results: Out of 425, 84.9% are males while 15.1% are females. Mean ages of onset of schizophrenia and substance misuse are 21.97+6 years and 17.99+7 years respectively. Age of onset of schizophrenia and substance misuse in males is 21.97+6.01 years and 17.99+7.06 years while in females it is 24.12+8.07 years and 19.45 +4.42 years respectively. Life time history for any substance misuse is 69.6%, tobacco 68.2% and non-tobacco substances 41.2%, cannabinoids 40.8%, opioids 5.2%, stimulants 5.7%, sedative hypnotics 2.6% and other substances 0.2%. 54.4% started substance misuse before the onset of schizophrenia while 12.5% started after the onset of schizophrenia. 65.9% are still (presently) misusing any substance, 65.4% are still misusing tobacco while 26.1% are still misusing non-tobacco substance. Substance misuse was more among uneducated, single and male patients. Conclusion: Substance misuse is quiet common among schizophrenic patients and its onset usually precedes the onset of schizophrenia. Onset of schizophrenia and substance misuse is earlier in males as compare to females. Moreover frequency of substance misuse is lower in female patients, those who are educated and those who are married and vice versa.